Strategi Pembinaan Mental Tradisi Kejuangan Prajurit Terhadap Situasi Global Guna Mendukung Tugas TNI AU - Waruwu, Erisman; Purwanto, Sigit; Widodo, Martinus Dwi Arjanto (Mahesa Research Center, 2025)
The development of struggle tradition mental training is a foundational pillar in shaping resilient and adaptive Air Force personnel in response to the dynamics of global challenges. This study aims to identify effective strategies in enhancing the mental readiness and resilience of Indonesian Air Force (TNI AU) soldiers in facing both internal and external threats. The research uses a qualitative descriptive-analytical method through interviews, observations, and document analysis. The findings reveal that mental development programs integrated with core values such as discipline, loyalty, perseverance, and unity—supported by methods like Santiaji, Santi Karma, religious activities, physical training, and psychological counseling—significantly improve the psychological and spiritual strength of the personnel. Moreover, the effectiveness of these programs is reinforced by supporting factors such as worship facilities, sports infrastructure, healthcare services, and strong command leadership. The study recommends systematic and continuous reinforcement of mental development programs across all Air Force units to shape professional, ethical, and globally responsive personnel.